2020
DOI: 10.1142/s0219455421500346
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Influences on Rail Corrugation of Metro Tangential Track

Abstract: Rail corrugation can reduce riding comfort by vibration and noise, and even cause running accident. In this paper, the vehicle–track coupled dynamic model was developed for a metro’s tangential track considering the wear in rail materials. The influences of different track structure parameters and vehicle speed on the generation and development of rail corrugation of the tangential track were analyzed using the developed model by the control variable method. The results show that for different parameters, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The under-rail structure composition and line layout of the track were set according to the target line so as to make the simulation results closer to reality. The general structural parameters of the vehicle model and track model are referred to the literature [34,35].…”
Section: Analysis Of Wheel-rail Stick-slip Characteristicsmentioning
confidence: 99%
“…The under-rail structure composition and line layout of the track were set according to the target line so as to make the simulation results closer to reality. The general structural parameters of the vehicle model and track model are referred to the literature [34,35].…”
Section: Analysis Of Wheel-rail Stick-slip Characteristicsmentioning
confidence: 99%
“…The results demonstrated that in the studied track system, the stiffness of the rail pad was the key factor affecting wheel-rail contact force. The literature [14] analyzed the influence of different track structure parameters and vehicle operation speed on the generation and development of rail corrugation on the straight track by using the control variable method. Based on the wheel-rail coupling effect, a practical model for predicting the growth of rail corrugation was proposed in the literature [15], the main cause of rail corrugation was studied, and the parameter analysis was carried out.…”
Section: Introductionmentioning
confidence: 99%